EFFECT OF TIME AND SUJI LEAF (Pleomele Angustifolia) ADITIVE CONCENTRATION ON THE CHARACTERISTIC OF CASSAVA BASED RICE ENRICHED WITH TUNA PROTEIN - Nurlina, Nurlina (The University of Lampung, 2015)
Food that has specially scent is more preferred by consumers. Analog rice that enriched with tuna flour have astench smell. Oneof themethodwas to relieve the stench smell is by soaking to suji leaf extract. The purpose of thisstudy is characteristic test of analog ricemade fromcassava flour enrichedwith protein of tuna, and investigatingthe effect of time and concentration of additives suji leaf with the physical and chemical properties of rice analog.Several parameters was evaluated such us protein content, moisture content, color, bulk density, uniformity ofgrain and organoleptic tests. This study used completely randomized factorial design. The first factor is time ofsoaking (5,10, and 15 minute) and the second factor is concentration of suji leaf extract (20, 40,60, and 80%).The ratio of cassava flour and protein of tuna in the research is 92,5%: 7,5%. The result showed that proteincontain of analog rice is 4,4687%. Moisture content of analog rice is between 10,48 – 12,61%. The longer ofsoaking time and high concentration canincreasedmoisture content of analog rice.Dominant colour analog riceis brown. Uniformity highest of granules produced on the size 1.7 – 3.33mesh. Treatment received by the panelbased ontest organoleptik by scent is treatment of analog rice that soakedwith 15minutes and ratioleaf suji 400:1000 g/ml.Keyword : Suji leaf, Scent, Rice analog, Protein.